Specificity of high-pure monocrystalline silicon production for various registering and converting devices - Trubitsyn, Yu.V.; Zverev, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
In this paper, recent results of studies focused on detector-grade silicon monocrystals production are summarized and systematized. Described are the manufacturing technology of silicon rod with a diameter up to 105 mm and dislocation-free monocrystals used for fabrication of large area detectors, p-type conductivity crystals with resistivity more than 1000 Ohm·cm being prepared by the method of neutron-transmutation doping.